Avaliação da viabilidade de doses inseminantes de suínos com maior sensibilidade ao resfriamento elaboradas com a adição de α-tocoferol - Schlösser, Luara Medianeira de Lima (2019)
The objective of this study was to evaluate the influence of the addition of α-tocopherol to inseminating doses of boars, selected for sensitivity to sperm cooling, prepared with Androstar® Plus diluent and stored at a temperature of 17ºC for up to 168 hours. Five ejaculates of 24 boars were analyzed for progressive sperm motility (PM) and classified into groups, according to the sensitivity to ejaculate in the cooling: PM <60% in 120 hours (greater), PM ≥60% in 120 hours and <60% in 168 hours (mean), and PM ≥60% in 168 hours (lower). After, the inseminating doses of the animals selected for the highest sensitivity to cooling received different concentrations of α-tocopherol: 0 (control) (T1), 100 μg / mL (T2) and 200 μg / mL (T3). From this, analyzes of motility, lipid peroxidation, plasma and acrosomal membrane integrity, and thermoresistance test (TTR) were performed. In relation to the mean of total motility (TM) in the evaluated treatments, T3 was more effective (85.19%), when compared to the control group (82.85%) and T2 (83.67%), respectively (P <0.05). The mean values of PM, local moility (LM) and fixed cells (IM) did not vary significantly (P> 0.05) between treatments. The mean values of TM and PM regressed significantly with the hours of storage (P <0.05), and LM and IM did not differ significantly (P> 0.05). In spermatic plasma and acrosomal membrane integrity, sperm cells with reacted acrosome and injured membrane differed (P <0.05) in the mean of the evaluation hours, that is, there was a marked increase in hour 168 (29, 96%) when compared to hour 72 (16.33%) of the analysis. Sperm cells with intact acrosome and integral membrane (AIMI) also differed (P <0.05) in the mean of the evaluation hours. We observed that at 168 hours there was a decrease in viable cells when compared to hour 72 (66.04% and 73.06%, respectively). The total motility (TM), evaluated by TTR, differed (P <0.05) in T3 (87.24%), when compared to T1 and T2 (84.43% and 85.22%, respectively). In the evaluation after 30 and 120 minutes of incubation at 38 °C, there was an increase (P <0.05) in TM (85.02% and 86.24%, respectively). The data related to total thiols, non-total thiols and ROS of the DI submitted to α-tocopherol treatments did not present differences (P> 0.05) between the treatments. The doses prepared from boars with greater sensitivity and submitted to the addition of 200 μg / mL of α-tocopherol maintained a good result regarding total motility, however, there was no such follow-up in relation to plasma and acrosomal membranes integrity, and reduction or maintenance of lipid peroxidation, during storage at 17 ° C for 168 hours. Therefore, it is possible to identify swine breeding males with greater sensitivity to cooling through the proposed methodology. The doses prepared from males with greater sensitivity and submitted to the addition of 200 μg/mL of α-tocopherol maintained a good result regarding total motility, however, there was no such follow-up in relation to plasma and acrosomal membranes integrity, and reduction or maintenance of lipid peroxidation, during storage at 17 ° C for 168 hours.